Device and corresponding method for selecting machinability data with artificial intelligence machinability - Wong, Shaw Voon (2003)
The present invention describes a device incorporating artificial intelligence and corresponding methods for recommending an optimal machinability data selection. The device comprises of a first component, which feeds the system with necessary input. A second component which is the main processing unit, acts as an inference engine to predict the outputs. The last component interprets the outputs, conveys the processed outputs to target location and converts them into necessary task. The input are identified as the machining operation, work piece material, machining tool type, and depth of cut. The outputs are the machining parameters, comprising of the optimal cutting speed and feed rate. The inference engine can be established with fuzzy logic, neural network of fuzzy-neural network.